Toxicity evaluation and anthelmintic potential of muntingia calabura L. (Aratiles) methanolic leaf extract - Casanova, Franzeska Rae M., Felix, Darlene Shaina N., Mendoza, John Mikhail R., Pamilar, Steffany Keith L., Villabroza, John Harold A. 4 0 16; 5
Abstract Soil-transmitted helminth (STH) infections remain a serious public health concern as it is one of the most common and neglected infections in the world. Recently, it has been discovered that there is a developing resistance to anthelmintic drugs which led to the increase of anthelmintic studies aimed at developing new drugs derived from plants. Muntingia calabura (aratiles) is a tree that thrives in tropical countries and is known to contain rich phytochemicals. In this study, the toxicity of aratiles crude methanolic leaf extract was assessed via brine shrimp lethality assay and its anthelmintic potential was investigated through the use of Eudrilus eugeniae as a representative organism for intestinal parasites. Qualitative phytochemical screening revealed the presence of phytochemical compounds such as alkaloids, flavonoids, tannins, terpenoids, and glycosides. Effect of the different concentrations of aratiles crude methanolic leaf extract (25%, 50%, 75%, and 100% concentrations) showed a concentration-dependent response trend which indicated that at higher concentrations, shorter mean paralysis and mean death times were recorded (at 100%, 18.33 and 80.39 minutes were noted for the mean paralysis and mean death time, respectively). All leaf extract concentrations were significantly different from each other, as well as when compared to mebendazole (p < 0.05). Results in the brine shrimp lethality assay revealed an LC50 value of 5.7052 ug/mL which is considered highly toxic based on the standard toxicity criterion. Keywords: Muntingia calabura, aratiles, Eudrilus eugeniae, phytochemicals, anthelmintic assay, brine shrimp lethality assay
Undergraduate Thesis: (Bachelor of Science in Biology) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2